Agama dan Intoleransi: Analisis Framing Kasus Penutupan Patung Bunda Maria di Kulon Progo Yogyakarta pada Berita Harian Kompas.Com - Siti Nurfadilah; M. Khusna Amal; Kun Wazis (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2023)
A number of mass media have a view of constructing reality through every report that occurs. The way the media works follows the ideology, vision and mission or rules of the game agreed upon by the owner of the media concerned, even in leading public opinion, they often build discourse using religious narratives as the instrument. As the recent hot discussion on digital media in March 2023 related to the closing of the statue of the Virgin Mary in Kulon Progo. The phenomenon of intolerance has sparked controversy, resulting in pros and cons in society. The media kompas.com was chosen as the research object considering that the owner is a follower of the Catholic religion and this is appropriate in describing the event of the closing of the statue of the Virgin Mary. This research aims to describe how religion is wrapped up in the kompas.com version of the news narrative and whether the kompas.com media is neutral in this case. This research method uses the framing analysis model of William A. Gamson and Andre Modigliani. The research results show that the framing carried out by the media kompas.com presents a dominant portion of religion as is the way the media in question works. The orientation of the coverage of the closure of the Virgin Mary statue in Kompas.com media is based on the framing analysis used to show the values ​​of tolerance, social media ethics and harmony between religions.